A report on practice in industry training in fish processing technology. - Guerrero, Adela Garcia (College of Fisheries, University of the Philippines, 1978)
The Philippines is surrounded by numerous bodies of water of varied areas. These territorial bodies of water are full of fish and other aquatic animals and plants. One of the main problems of the fishery industries is how to preserve fish caught from our waters as well as other fishery products. Various methods of preservation have been employed to lengthen the storage time and keeping quality of fish among them, freezing, salting, smoking, drying, etc. it is for this reason that fish preservation methods and techniques, their advantages and disadvantages. Motivated by the growing need for technically trained personnel in the fishery industries, one of the requirements for graduation is to undergo training in these different fields. In this way, the students would be able to apply or put into practice the theories they learned in would be able to apply or put into practice the theories they learned in school. They are made aware of the existing practices of fish processing in the country, and at the same time, trained to think of ways of improving such practices if there is a need for it. The following is a brief compilation of reports on the training undergone by the author in the different fish processing plants visited.